Hambatan Komunikasi Organisasi Pada Layanan Antar Di Borma Cikutra - Aldi Ramadan; Ridma Meltareza; Taufiq Muharamsyah (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
This research aims to understand the course of communication in an organization and organizational communication barriers in delivery services at Borma Cikutra. The study used a qualitative approach with descriptive methods. Information gathering techniques were carried out through comprehensive interviews, observations, and document collection. The informants in this study consisted of consisted of delivery service admins and warehouse staff directly involved in delivery service operations at Borma Cikutra. Data analysis techniques used the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results showed that organizational communication in delivery services occurs through vertical, horizontal, and diagonal communication involving delivery service admins, warehouse staff, cashiers, couriers, and customers. The main communication media used are WhatsApp and HT (Handy Talky). Communication barriers found include semantic, technical, and organizational barriers. Semantic barriers are the most dominant obstacle due to unclear and incomplete customer order information. Communication barriers impact service delays, service errors, and increased communication burden on delivery service admins. Efforts to overcome communication barriers include reconfirming customer orders, rechecking goods, improving employee coordination, and implementing responsive service communication.